The Ancestral Possession. The Tromba Cult on the Island of Saint-Marie - Kwapień, Joanna (Interdisciplinary Studies in Musicology, 2026)
The article examines the tromba cult – a spirit possession ritual practiced in Madagascar, with particular focus on the island of Sainte-Marie (Nosy Boraha). Drawing on ethnographic fieldwork conducted in July 2024, the study explores the cultural and religious context of ancestral possession, the structure and performance of tromba ceremonies, and the essential role of music in facilitating spirit possession. The research discusses the Malagasy belief system concerning ancestral spirits (razana), the historical origins of the tromba cult among the Sakalava people, and the ritual’s contemporary manifestations. Special attention is given to the musical elements of the ceremony, including the use of traditional instruments such as the valiha, accordion, and kaiamba rattles, and their function in inducing and sustaining trance states through polyrhythmic structures and vocal invocations. The article also addresses the performative nature of tromba.